Clusters and Comparative Advantage: Implications for Industrial Policy - Andrés Rodríguez-Clare (Inter-American Development Bank, Research Department, 2005)
Industrial agglomerations or `clusters` arise in the presence of industry-specific and local externalities, also called Marshallian externalities. The standard argument is that such externalities may justify a policy of infant-industry protection to allow and encourage clusters to emerge. This paper explores that argument and shows that different policy implications emerge under a more realistic modeling of clusters. In particular, rather than distorting prices to promote clusters in `advanced`sectors that may exhibit strong clustering possibilities, countries should focus instead on promoting clustering in current sectors that have demonstrated the strongest comparative advantage. Import substitution is not a proper way to achieve such a goal.
Keywords: 330; Regionales Cluster; Komparativer Vorteil; Industriepolitik; Importsubstitution; Theorie